(untitled) (International Journal of Food and Nutritional Sciences, 2022)
It is widely believed that faculty members are the most revered resource in any educational institution and shoulder the responsibility of shaping the future of both the students and the institute itself. However, the problem surfaces when this rich resource of talent leaves the institute and moves to the competing institutes, which affects the overall student development, teaching and training activities, brand and goodwill of the institute, cost of training and re-training of the new faculty members, lecture scheduling and administrative work etc. The above problem is seen to be quite acute in the private higher education institutes. This paper makes a modest attempt to explain the factors that contribute to faculty attrition and study the current practices of retention implemented by educational institutes. The paper also evaluates the new strategies related to Stay Interviews used by higher educational institutes to retain faculty members. The primary data, collected from fifty faculty members of different higher management education institutes of Maharashtra, have been analysed for achieving the study objectives.